Leveraging cultural diversity in emerging markets - Goncalves, Marcus; Majlergaard, Finn. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Leveraging cultural diversity is an important element for competing in the global market. Understanding the overall macroeconomic landscape of emerging and frontier markets is also very important in enabling corporation and international business professionals to fully realize the potential for strategic globalization, which empowers them to compete globally. Most transnational and multinational corporations have made substantial progress in their globalization efforts by establishing operations in several countries and offshoring certain processes or functions to countries with capabilities and growth potential. However, while these recent globalization efforts have their roots in cost arbitrage, today, successful companies must understand that globalization can be a means for shoring up competitive advantage not only to lower labor costs but more importantly to diversify intellectual capabilities and growth, and improve quality enhancement opportunities, in addition to enhancing the ability to get products to market more quickly. This book looks at how one can move forward from the current situation. Most people still see cultural differences as a barrier to success. This book demonstrates how one can, instead, leverage from the cultural diversity and create better, more competitive companies, better leaders, and hopefully a safer and more sustainable world.
1. Understanding emerging markets -- 2. Economic and cultural transformations at emerging and frontier markets -- 3. Coping with differences and promoting interactions -- 4. Clash of civilizations or cultural synergies? -- 5. Global individualism -- 6. Western or Christian and Muslim or Arab heading towards inevitable conflicts: really? -- 7. Benefiting from cultural synergies -- 8. Commonalities in cultures: fruitful reconciliations -- 9. Emerging markets do not want to be like the West -- 10. The lesser importance of national cultural identities -- About the authors -- Advance quotes for Leveraging cultural diversity in emerging markets -- References -- Bibliography -- Index.
Includes bibliographical references (pages 205-218) and index.
Title from PDF title page (viewed on December 26, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Cultural pluralism -- Developing countries; Globalization; International business enterprises; Developing countries -- Economic conditions; Cultural Diversity; Emerging Markets; Global Individualism; Multiculturalism; Electronic books